Visual Media, Macro Photography, and Exponential Imagination: Scalar Views in Ecohumanism - Ulmer, Jasmine Brooke (Journal of Ecohumanism, 2023)
This brief essay engages with environmental stewardship and scale in the Anthropocene. Taking inspiration from Kees Boeke’s illustrated children’s book Cosmic View: The Universe in 40 Jumps and Charles and Ray Eames’s Powers of Ten—a short film based on Boeke’s book—this photo essay illustrates how, through the production of eco-art, the practice of macro photography can suggest the presence of worlds within one’s world. Creative engagements are offered so that children and adults, who must all live through and contend with the Anthropocene, might appreciate notions of environmental scale, particularly in relation to our ecological footprints over time. In so doing, visual media such as illustrated books, films, and macro photography encourage sustainability on a larger scale than humanity has yet to imagine.